2018
DOI: 10.1159/000490117
|View full text |Cite
|
Sign up to set email alerts
|

Ghost Infarct Core and Admission Computed Tomography Perfusion: Redefining the Role of Neuroimaging in Acute Ischemic Stroke

Abstract: Background: Determining the size of infarct extent is crucial to elect patients for reperfusion therapies. Computed tomography perfusion (CTP) based on cerebral blood volume may overestimate infarct core on admission and consequently include ghost infarct core (GIC) in a definitive lesional area. Purpose: Our goal was to confirm and better characterize the GIC phenomenon using CTP cerebral blood flow (CBF) as the reference parameter to determine infarct core. Methods: We performed a retrospective, single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 28 publications
6
103
1
Order By: Relevance
“…Recent studies had suggested that CTP core infarct may not necessarily represent irreversibly dead tissue. 11,13 However, multiple factors play a role in this overestimation of infarct core: time from symptom onset to CTP, size of the infarct core, postprocessing software package, the time between CTP and reperfusion, and the completeness of reperfusion are a few of these factors. [15][16][17][18][19] Size of the initial infarct core influences accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies had suggested that CTP core infarct may not necessarily represent irreversibly dead tissue. 11,13 However, multiple factors play a role in this overestimation of infarct core: time from symptom onset to CTP, size of the infarct core, postprocessing software package, the time between CTP and reperfusion, and the completeness of reperfusion are a few of these factors. [15][16][17][18][19] Size of the initial infarct core influences accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have suggested that CBV maps reliably predict the final infarct on follow‐up imaging . On the contrary, some other studies have called the reliability of CTP into question …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that reduced relative CBF of less than 30% accurately estimates final infarct volume on diffusion-weighted imaging magnetic resonance imaging (DWI MRI) [8], while others have shown ischemic core overestimation with the same parameter, illustrating the so-called "ghost core infarct" concept [9,10]. A more recent trial utilized prospectively collected data from the Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials (HERMES) and the Tenecteplase Versus Alteplase Before Endovascular Therapy for Ischemic Stroke (EXTEND-IA TNK) trials to retrospectively determine DWI and CTP CBF < 30% differences in patients who achieved early, good revascularization of a LAO [11].…”
Section: Introductionmentioning
confidence: 99%
“…33 In some cases, particularly in early presentations, CTP may overestimate core infarct size (aka "ghost core"), which could incorrectly deny patients from receiving life-altering therapy. 63,64 For this reason, when the CTP and the ASPECTS are discordant, it is reasonable to proceed to thrombectomy if ASPECTS score is acceptably high, usually ! 6.…”
mentioning
confidence: 99%